2020
DOI: 10.1002/jsfa.10654
|View full text |Cite
|
Sign up to set email alerts
|

Processing method modulates the effectiveness of black beans for lowering blood cholesterol in spontaneously hypertensive rats

Abstract: BACKGROUND: Various foods are known to have beneficial effects on health when consumed whole; however, there is a trend towards preparing foods from processed ingredients, and it remains unclear whether the benefits of the whole food are retained. The purpose of this study was therefore to examine whether different processing techniques affect the lowering of cholesterol and the vascular effects of black beans (Phaseolus vulgaris L.). RESULTS: Beans were prepared by overnight soaking and boilingthe standard me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It was previously reported that 60% ethanol extracts of black soybeans improved TC, LDL-C, and HDL-C in overweight and obese adults in a randomized, double-blinded clinical trial [ 42 ]. Likewise, black soybeans processed by various methods, including boiling, freeze-drying, and coarse-milling, decreased TC and LDL-C levels in SHR [ 43 ]. Besides, a 40% ethanol fraction of hot-water extracts of adzuki beans improves hepatic lipid profiles with a reduction of TG (12%) and TC (7%) in the KKAy mice model [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that 60% ethanol extracts of black soybeans improved TC, LDL-C, and HDL-C in overweight and obese adults in a randomized, double-blinded clinical trial [ 42 ]. Likewise, black soybeans processed by various methods, including boiling, freeze-drying, and coarse-milling, decreased TC and LDL-C levels in SHR [ 43 ]. Besides, a 40% ethanol fraction of hot-water extracts of adzuki beans improves hepatic lipid profiles with a reduction of TG (12%) and TC (7%) in the KKAy mice model [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Common bean effect on hypercholesterolemia may be due also to its RS concentration, as also partly found by various authors modulating the presence of the RS from bean in model rats (Tanaka et al, 2019;Kilua et al, 2020;Zuo et al, 2022). Loader et al (2021) found scarce effect of various dies containing variable bean RS concentration on the body weight, blood pressure, and aorta morphology, but found a reduction of the fasting total cholesterol or low-density lipoprotein cholesterol International Journal of Food Science and Technology 2023 depending on either the bean cooking strategies and presence of bean in the diet. Unluckily, the former authors were unable to attribute the health effects to the presence of the RS or other fibres.…”
Section: Lipid Metabolism and Weight Control And Activity Of "Starch ...mentioning
confidence: 64%
“…For example, and regarding hypertension, Loader et al (2021) found that micronized, but not extruded bean lowered the cholesterol of spontaneously hypertensive rats and such difference was not linked to either the amount or composition of DF or RS in both products.…”
Section: Nutritional Health and Sensory Aspects Of Bean Rsmentioning
confidence: 99%
See 2 more Smart Citations